Task Technology Fit in Hemodialysis Care: A Comparative Evaluation of the Renalmu.com Application in Indonesian Hospitals - Umi Khoirun Nisak; Irwan Alnarus Kautsar; Yahya Arif Nugroho; Aditiawardana Aditiawardana; Hamid Al-Tameemmi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Hemodialysis services are essential for patients with end-stage renal disease (ESRD), offering routine treatment to sustain health and enhance quality of life. As the prevalence of ESRD continues to rise, hemodialysis units must focus on delivering high-quality care, optimizing resource management, and ensuring patient satisfaction. To support these goals, this study employs a quantitative comparative design with a cross-sectional approach to assess the effectiveness of the Renalmu.com application in hemodialysis services. The study will include 30 respondents from two hospitals, with data analysed using the Mann-Whitney U test to compare key variables. Data collection is scheduled to begin in September 2024 and conclude in March 2025. Preliminary results from the Mann-Whitney U test indicate that while both hospitals reported similar experiences across most dimensions of the Renalmu.com application, a significant difference was observed in the Task Technology Fit (TTF) dimension of data quality. Hospital 1 demonstrated superior data quality, reflected by a U-value of 56.500 and a p-value of 0.013. No significant differences were found in other TTF dimensions, including task characteristics (non-routine, interdependence), site graphic attractiveness, privacy/security, interactivity, data locability, authorization, compatibility, product timeliness, reliability, ease of use, and user relationships. These findings suggest that the primary distinction between the two hospitals lies in the effective utilization of data quality to support clinical decision-making in hemodialysis treatment Keywords: Task-Technology Fit, Dialysis, Quality Service improvement